2018
DOI: 10.17576/jsm-2018-4710-07
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fermentation Time and Turning Intervals on the Physicochemical Properties of Rambutan (Nephelium lappaceum L.) Fruit Sweatings

Abstract: Sweatings, the exudates that leach out from fermenting fruits during rambutan fruit fermentation are considered as a waste by-product and are allowed to be drained off. This could lead to a pollution problem. Besides, it is a waste if the sweatings are possible to be transformed into food products and ingredients. However, prior transformation, the fundamental knowledge of the sweatings should be understood. Hence, the main aim of this study was to investigate the physicochemical properties of sweatings as aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The result indicate that the pH of the RS external peel was significantly more acidic (p<0.05) than RT, ranging from 4.17 to 4.25. These findings were aligned with previous research conducted by Chai et al (2018a), who reported a pH range of 4.18 to 4.25 for rambutan peel. Lufu, Ambaw and Opara (2020) stated that pH values can be influenced by factors such as rain and ambient humidity.…”
Section: Weight Of Visible Fine Dirt (Mg)supporting
confidence: 91%
See 2 more Smart Citations
“…The result indicate that the pH of the RS external peel was significantly more acidic (p<0.05) than RT, ranging from 4.17 to 4.25. These findings were aligned with previous research conducted by Chai et al (2018a), who reported a pH range of 4.18 to 4.25 for rambutan peel. Lufu, Ambaw and Opara (2020) stated that pH values can be influenced by factors such as rain and ambient humidity.…”
Section: Weight Of Visible Fine Dirt (Mg)supporting
confidence: 91%
“…Peeling the rambutan's peel will reveal the sweet, gelatinous white pulp that clings to the seeds (Li, Zeng & Shao 2018;Prakash 2021). The pulp is delicious, soft, juicy, firm, and rich in vitamin C (Chai et al 2018a) (Figure 1). Rambutan Anak Sekolah or known as Clone R191 is one of the most well-known and delicious rambutan clones, which was first cultivated in Thailand.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…High-Performance Liquid Chromatography (HPLC) (Shimadzu, Japan) with a Refractive Index detector and a Purospher Star NH 2 column (259 mm × 4.6 mm, particle size of 5 µm) was used to determine the sugar content (Chai et al, 2018a(Chai et al, , 2020. Ten grams of homogenized sample was treated with 100 ml of 85% methanol for 30 min at 80 ºC in a water bath.…”
Section: Sugar Composition and Contentmentioning
confidence: 99%